Advancing banana and plantain R & D in Asia and the Pacific: Proceedings of the 9th INIBAP-ASPNET Regional Advisory Committee meeting held at South China Agricultural University, Guangzhou, China, 2-5 November 1999. - Molina, A.B.; Roa, V.N.; International Network for the Improvement of Banana and Plantain (2000)
For the first time the proceedings of the meeting of the ASPNET Regional Advisory Committee are published in the form of a book of 154 pages. This publication presents the latest news on Musa research, development and future prospects from Malaysia, Indonesia, the Pacific Islands, Sri Lanka, Bangladesh, the Philippines and a more in depth account from China. It also provides updates on the state of banana cultivar names and synonyms in Southeast Asia, the results of studies on nematode on the most common banana cultivars in Vietnam, the biodiversity of wild Musaceae in Northern Thailand and recent developments in Fusarium research in Taiwan.